Preparation of cross-linked enzyme aggregates of L-aminoacylase via co-aggregation with polyethyleneimine - Vaidya, Bhalchandra K.; Kuwar, Suyog S.; Golegaonkar, Sandeep B.; Nene, Sanjay N. (Journal of Molecular Catalysis B-Enzymatic, 2012)
L-Aminoacylase from Aspergillus melleus was co-aggregated with polyethyleneimine and subsequently cross-linked with glutaraldehyde to obtain aminoacylase-polyethyleneimine cross-linked enzyme aggregates (termed as AP-CLEA). Under the optimum conditions, AP-CLEA expressed 74.9% activity recovery and 81.2% aggregation yield. The said method of co-aggregation and cross-linking significantly improved the catalytic stability of L-aminoacylase with respect to temperature and storage. AP-CLEA were employed for enantioselective synthesis of three unnatural amino acids (namely: phenylglycine, homophenylalanine and 2-naphthylalanine) via chiral resolution of their ester-. amide- and N-acetyl derivatives. The enantioselectivity of AP-CLEA was the highest for hydrolysis of amino acid amides; was moderate for hydrolysis of N-acetyl amino acids and was the least for hydrolysis of amino acid esters. Furthermore, AP-CLEA were found to retain more than 92% of the initial activity after five consecutive batches of (RS)-homophenylalanine hydrolysis suggesting an adequate operational stability of the biocatalyst. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: chiral resolution; Cross-linked enzyme aggregates; L-Aminoacylase; Polyethyleneimine; Unnatural amino acids

Immobilization of pectinase on reusable polymer support for clarification of apple juice - Rajdeo, Kishor; Harini, Tirunagari; Lavanya, Kuna; Fadnavis, Nitin W. (Food and Bioproducts Processing, 2016)
Pectinase (E.C.3.2.1.15) was successfully immobilized on recyclable polymer matrix. The immobilization matrix was prepared by reaction of polyethyleneimine (mol. wt. 70,000) with epoxy-activated acrylate copolymer DILBEAD-VWR. The enzyme pectinase was first adsorbed on the polymer at pH 7.0 via ion exchange and then stabilized by crosslinking with dextran aldehyde. While the free enzyme shows a pH-optimum of 5.0, the immobilized enzyme exhibited high level of activity in a broad pH range of pH 3.0-7.0. Although the thermal stability of free and immobilized enzymes was similar, at room temperature, the immobilized enzyme could be recycled more than 10 times with loss of less than 5% of its activity during clarification of apple juice. On the eventual loss of enzyme activity, the immobilized enzyme and dextran aldehyde can be easily removed from the polymer by a simple treatment with 1N HCl and the polymer can be reused for immobilization of a fresh batch of enzyme. This support also can be reused several times, making the process economically attractive. The properties of apple juice treated with immobilized enzyme were similar to those of that treated with free pectinase. (C) 2016 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Apple juice; Dextran aldehyde; Immobilization; Pectinase; Polyethyleneimine; Polymer

Fabrication of bacterial nanocellulose/polyethyleneimine (PEI-BC) based cationic adsorbent for efficient removal of anionic dyes - Thorat, Meghana N.; Jagtap, Ashish; Dastager, Syed G. (Journal of Polymer Research, 2021)
A bacterial cellulose (BC) based adsorbent was prepared by using polyethyleneimine (PEI) using epichlorohydrin as a cross-linker. The physicochemical characterization of the of the developed adsorbent was carried out using FTIR, BET analysis and SEM, respectively. The dye removal efficiency of the adsorbent was assessed towards two anionic model dyes viz. congo red (CR) and reactive red 120(RR). The kinetic data for the removal of both the anionic dyes were fitted better using pseudo-second-order model. Langmuir model describes well the process of adsorption with predicted maximum adsorption capacity (q(max)) 515.46 and 300.3 mg L-1 for CR (at pH 6.0) and RR (at pH 3.0) respectively. The adsorption-desorption study showed that PEI-BC adsorbent is effective with more than 90% dye removal efficiency even after four cycles. Furthermore, the bactericidal activity of the adsorbent was analysed using Escherichia coli and Staphylococcus aureus and adsorbent showed good inhibition against both test organisms. The study reveals that PEI-BC adsorbent can be a good candidate for water remediation purpose bearing multifunctional behaviour.
Keywords: adsorbent; Anionic dyes; Bacterial cellulose; Bactericidal; Polyethyleneimine